Effect of internal bulkheads on skirt-soil interaction during jacking installation of a novel skirted foundation in sand: a two-scale experimental investigation - Zhen Yan; Yifan Liu; Dengfeng Fu; Mingsen Jiang (Ocean Engineering, 2026)

Aggregate status determining the foaming behavior of phycocyanin: insights from bulk phase and air–water interface structure - Qingxuan Fu; Jingjing Wang; Fangcheng Jiang; Wangyang Shen; Ji'an Xia; Dengfeng Peng; Weiping Jin (Food Chemistry, 2026)

Tracking Cretaceous to present day deep-sea sedimentary hiatuses driven by intensified bottom-water currents - Jiewei Hu; Dengfeng Li; David Chew; Simon W. Poulton; Yanhui Dong; Jinzhou Peng; Yu Fu; Xiaoming Sun (Earth and Planetary Science Letters, 2026)

Load-bearing behavior and failure envelope of a novel staged telescopic suction anchor foundation in silty sand: A numerical study - Haoyu Wang; Lele Liu; Dengfeng Fu; Dong Wang (Ocean Engineering, 2026)

Organic matter controls rare earth element hyper-enrichment in Pacific deep-sea bioapatite - Xijiao Liao; Dengfeng Li; Simon W. Poulton; John R. Reinfelder; David Chew; Yu Fu; Yongjia Liang; Zhengkun Li; Jinzhou Peng; Xiaoming Sun (Geochimica et Cosmochimica Acta, 2026)

Upper-bound solutions for capacity of a catenary-moored suction caisson in clay - Dingtao Yan; Yue Yan; Zhechen Hou; Dengfeng Fu; Dong Wang (Computers and Geotechnics, 2026)

Generalised analytical solution for suction-driven seepage during suction caisson installation in soils with spatially varying permeability - Dingtao Yan; Dengfeng Fu; Zhechen Hou; Yue Yan; Dong Wang (Ocean Engineering, 2026)

Bearing capacity and optimization of finned suction caissons in clay - Ruizhe Xu; Shuntao Fan; Yue Yan; Dengfeng Fu (Ocean Engineering, 2026)

Numerical investigation: Undrained capacity of a hybrid anchor under VHMT combined loading in clay - Fengwei Yang; Maolin Li; Dengfeng Fu; Yue Yan; Dong Wang (Ocean Engineering, 2026)

Nanocellulose improves the texture profiles of gluten-free bread through filler reinforcement and gas cell stabilization - Yu Chen; Qingxuan Fu; Zhan Li; Wangyang Shen; Jinling Li; Dengfeng Peng; Weiping Jin (Food Hydrocolloids, 2026)

Upper-bound solutions for capacity of tracked vehicles on clay under fully three-dimensional loading - Dingtao Yan; Yue Yan; Dengfeng Fu; Dong Wang (Transportation Geotechnics, 2026)

Research on the Bearing Performance of Suction Pile–Gravity Hybrid Foundation in Sand Under Multi-Directional Loading - Yangming Chen; Maolin Li; Zhechen Hou; Fengwei Yang; Dengfeng Fu (Journal of Marine Science and Engineering, 2026)
The suction pile–gravity hybrid foundation (SPGH) has emerged as a novel foundation for floating wind turbines (FWTs) due to its superior bearing mechanism. In harsh marine environments, offshore wind turbine structures endure multidirectional wave–wind current loads, which are transmitted through mooring systems as complex multidirectional coupled loads (horizontal, vertical, bending moments, and torque), imposing severe challenges to the bearing capacity. Therefore, this study carries out 3D finite element simulations, utilizing the Hardening Soil–Small Strain constitutive model to simulate the stress–strain behavior of sand, to systematically investigate the failure modes and bearing capacity of SPGH foundations. The method underlying the failure envelope theory is proposed, applicable to tension-leg mooring systems (dominated by uplift and lateral loads) and catenary mooring systems (dominated by compression and lateral loads). Results indicate that under pure vertical uplift or torque loading, both SPGH and traditional SP foundations exhibit typical interfacial shear failure modes. Under pure horizontal or bending moment loading, SPGH and SP foundations exhibit rotational instability failure. The direction of vertical load has a significant impact on the bearing performance of SPGH foundations. In addition, horizontal load can increase its vertical uplift-bearing capacity by 46% and torque capacity by 48%. The enhancement effect of the bending moment load is more significant, and can increase the vertical uplift-bearing capacity by 115% and the torque-bearing capacity by 112%, respectively, while vertical downward loads within a certain range significantly improve horizontal and bending-bearing performance.

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Retention of fracturing fluid in shale oil formations based on 1D- and 2D-NMR: Implications to shale oil production - Xiao Yan; Zhenkai Huang; Zengmin Lun; Jiangna Fu; Tao Zhang; Chunpeng Zhao; Heng Wang; Yibing Xie; Chunyan Fan; Dengfeng Zhang; Jie Zou (Fuel, 2026)

Response of offshore wind turbine tripod suction bucket foundation under wind and multi-directional seismic loading conditions - Dingtao Yan; Rui Liu; Yue Yan; Dengfeng Fu; Dong Wang (Computers and Geotechnics, 2026)

Simple methods for imperfection sensitivity analysis of caisson skirts under suction installation - Ruizhe Xu; Yurong Zhang; Dengfeng Fu; Yue Yan; Wentao Cui; Shuntao Fan; Dong Wang (Computers and Geotechnics, 2026)

Investigation of undrained axial resistance of subsea pipelines considering effects of soil berm formation, strain softening, and rate dependence - Weini Zhao; Huan Zhao; Yue Yan; Dengfeng Fu; Yinghui Tian (Ocean Engineering, 2025)

An innovative boundary surface model integrating strain rate effect and its application in assessing sliding resistance of a movable subsea mudmat - Zhong Xiao; Zongquan Li; Pan Hu; Xiang Wang; Dengfeng Fu; Zhifa Yu; Xu Liu (Soil Dynamics and Earthquake Engineering, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Advances in Marine Geological and Geotechnical Hazards - Lele Liu; Qingbing Liu; Dengfeng Fu (Journal of Marine Science and Engineering, 2025)
Since the first hearth was kindled, energy has steered human destiny, and today the ocean offers its own vast portfolio [...]

Buckling characteristics of bucket foundations under suction installation in spatially variable clay - Shuntao Fan; Lingyu Fan; Yue Yan; Dengfeng Fu; Sa Li (Computers and Geotechnics, 2025)

Buckling characteristics analysis of bucket foundations under suction installation considering geometric and installation depth effects - Dengfeng Fu; Ruizhe Xu; Shuntao Fan; Ruolin Yuan; Yue Yan; Zefeng Zhou (Ocean Engineering, 2025)

Numerical investigation to contribution of peripheral skirt and frame on undrained capacity of framed-tripod hexagonal bucket foundation in clay - Bo Liu; Jinrun Wang; Dengfeng Fu (Ocean Engineering, 2025)

Mild acid extraction of Camellia protein with low saponin: Composition identification and interfacial stabilization - Xiaoli Yang; Jisong Zhou; Qingxuan Fu; Weiping Jin; Wangyang Shen; Yaoqi Tian; Dengfeng Peng (Food Hydrocolloids, 2025)

Stiffness evaluation of bucket foundation considering the effect of adjacent spudcan penetration and pullout - Huan Zhao; Dengfeng Fu; Yue Yan; Xiaogang Guo; Zefeng Zhou (Computers and Geotechnics, 2025)

Numerical study of cone penetration tests to predict effective internal friction angles of cohesive soils - Wenli Zhang; Dong Wang; Jingbin Zheng; Dengfeng Fu (Engineering Geology, 2025)

Prediction of the potential tilt of tripod-bucket jacket foundation considering the effect of spudcan installation - Dengfeng Fu; Xiaogang Guo; Huan Zhao; Yue Yan; Zefeng Zhou (Ocean Engineering, 2024)

Engineering Properties of Marine Soils and Offshore Foundations - Youkou Dong; Dengfeng Fu; Xiaowei Feng (Journal of Marine Science and Engineering, 2024)
To reduce greenhouse gas emissions and enhance energy security, the role of renewable energy in the global energy structure is becoming increasingly significant [...]

Estimation of breakout force of spudcan footing in structured clay - Yanan Xie; Dong Wang; Jingbin Zheng; Dengfeng Fu; Kuntan Chang (Ocean Engineering, 2024)

Nonlocal regularized analyses for keying of strip plate anchors in strain-softening clay - Huimin Pei; Dong Wang; Dengfeng Fu (Ocean Engineering, 2024)

Responses of physico-chemical properties and CH4 adsorption/desorption behaviors of diverse rank coal matrices to microwave radiation - Xing Tang; Xuexiang Fu; Jie Zou; Dengfeng Zhang (Gas Science and Engineering, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Design method of geotechnical capacity for tripod suction bucket foundations in clay - Weichen Wang; Dengfeng Fu; Yue Yan; Zefeng Zhou (Computers and Geotechnics, 2024)

Bearing capacity of the gravity tripod foundation under general loading in clay - Jinrun Wang; Yue Yan; Dengfeng Fu; Zefeng Zhou (Ocean Engineering, 2024)

Effects of phosphate on REY adsorption by goethite: Insights into REY enrichment and release in marine iron oxyhydroxides during early diagenesis - Yongjia Liang; Xiaoming Sun; Dengfeng Li; Caroline L. Peacock; Yu Fu (Chemical Geology, 2024)

Role of probiotics/synbiotic supplementation in glycemic control: A critical umbrella review of meta-analyses of randomized controlled trials - Dengfeng Xu; Lingmeng Fu; Da Pan; YiFang Chu; Meiyuan Feng; Yifei Lu; Chao Yang; Yuanyuan Wang; Jiayue Xia; Guiju Sun (Critical Reviews in Food Science and Nutrition, 2024)

Estimation of Effective Internal Friction Angle by Ball Penetration Test: Large-Deformation Analyses - Bohan Zhou; Wenli Zhang; Dong Wang; Dengfeng Fu (Journal of Marine Science and Engineering, 2024)
The ball penetrometer is a full-flow penetrometer used as an alternative to the traditional cone penetrometer for characterizing the strength of soft sediments, particularly for offshore engineering, due to its large projection area. However, if the ball is penetrated under partially drained conditions, the resistance of the ball changes with the penetration velocity. The performance of ball penetration is examined employing a coupled large-deformation finite-element method. The reliability of numerical simulations under undrained and partially drained penetrations is verified by comparing with previous tests in the chamber and centrifuge. The backbone curve determining the penetration resistance on the spherical probe is proposed to quantify the influence of partially drained conditions, which captures the effect of the ratio of the diameters of the shaft and ball. Base on the backbone curve derived, an interpretation approach is proposed to predict the effective internal friction angle using the net resistance measured in the ball penetration tests with different penetration velocities.

Source, composition and molecular diversity of dissolved and particulate organic matter varied with riparian land use in tropical coastal headstreams - Hengkuan Ji; Hua Wang; Zhipeng Wu; Dengfeng Wang; Xilong Wang; Peijiao Fu; Caisheng Li; Wangang Deng (Science of The Total Environment, 2024)

Vertical Monotonic and Cyclic Responses of a Bucket in Over-Consolidated Clay - Jun Jiang; Dong Wang; Dengfeng Fu (Journal of Marine Science and Engineering, 2023)
Bucket foundations, especially multi-bucket foundations, have become an alternative for large offshore wind turbines. Vertical responses of a single bucket are critical for the serviceability design of tripod or tetrapod bucket foundations. Centrifuge tests are conducted to investigate the responses of a single bucket under monotonic and symmetric cyclic loading in over-consolidated clay. The strength of clay is obtained by cone penetration tests. The monotonic vertical capacity measured in the centrifuge tests are compared with the finite element results, with errors less than 6%. The effects of the ratio of cyclic loading amplitude to vertical capacity (ranging between 0.37 and 0.64) and the number of cycles on the accumulation of vertical displacement and evolution of stiffness are explored. Simplified functions are proposed to predict the evolutions of dimensional and dimensionless stiffness.

Electrospun Ce–Mn oxide as an efficient catalyst for soot combustion: Ce–Mn synergy, soot-catalyst contact, and catalytic oxidation mechanism - Yuxi Liao; Peng Liu; Jun Zhang; Can Wang; Longwen Chen; Dengfeng Yan; Quanming Ren; Xiaoliang Liang; Mingli Fu; Suib Steven L.; Daiqi Ye (Chemosphere, 2023)

Mechanoluminescent optical fiber sensors for human–computer interaction - Biyun Ren; Bing Chen; Xianhui Zhang; Honglei Wu; Yu Fu; Dengfeng Peng (Science Bulletin, 2023)

PL57 garnet as a new natural reference material for in situ U–Pb isotope analysis and its perspective for geological applications - Dengfeng Li; Yu Fu; Pete Hollings; Roger H. Mitchell; Shannon Zurevinski; Sandra Kamo; Rongqing Zhang; Yu Zhang; Qiaofen Liu; Jianlin Liao; Yongjia Liang; Xiaoming Sun (Contributions to Mineralogy and Petrology, 2022)

Cyclic response of monopile-supported offshore wind turbines under wind and wave loading in sand - Rui Liang; Yu Yuan; Dengfeng Fu; Run Liu (Marine Georesources & Geotechnology, 2021)

Numerical Investigation to the Effect of Suction-Induced Seepage on the Settlement in the Underwater Vacuum Preloading with Prefabricated Vertical Drains - Shu Lin; Dengfeng Fu; Zefeng Zhou; Yue Yan; Shuwang Yan (Journal of Marine Science and Engineering, 2021)
Vacuum preloading combined with prefabricated vertical drains (PVDs) has the potential to improve the soft sediments under water, however, its development is partly limited by the unclear understanding of the mechanism. This paper aims to extend the comprehension of the influential mechanism of overlapping water in the scenario of underwater vacuum preloading with PVDs. The systematic investigations were conducted by small strain finite element drained analyses, with the separated analysis schemes considering suction-induced consolidation, seepage and their combination. The development of settlement in the improved soil region and the evolution of seepage flow from the overlapping water through the non-improved soil region into improved zone are examined in terms of the build-up of excess pore pressure. Based on the results of numerical analyses, a theoretical approach was set out. It was capable to estimate the time-dependent non-uniform settlement along the improved soil surface in response to the combined effects of suction-induced consolidation and seepage. The difference of underwater and onshore vacuum preloading with PVDs is discussed with some practical implication and suggestion provided.

Bearing performance of offshore bucket foundation with internal cruciform skirt under combined loading - Zhong Xiao; Ying Liu; Borui Ge; Dengfeng Fu; Zengfeng Zhou; Yue Yan (Marine Georesources & Geotechnology, 2020)

Effect of Gain in Soil Friction on the Walking Rate of Subsea Pipelines - Zhaohui Hong; Dengfeng Fu; Wenbin Liu; Zefeng Zhou; Yue Yan; Shuwang Yan (Journal of Marine Science and Engineering, 2019)
Subsea pipelines are commonly employed in the offshore oil and gas industry to transport high-pressure and high-temperature (HPHT) hydrocarbons. The phenomenon of pipeline walking is a topic that has drawn a great deal of attention, and is related to the on-bottom stability of the pipeline, such as directional accumulation with respect to axial movement, which can threaten the security of the entire pipeline system. An accurate assessment of pipeline walking is therefore necessary for offshore pipeline design. This paper reports a comprehensive suite of numerical analyses investigating the performance of pipeline walking, with a focus on the effect of increasing axial soil resistance on walking rates. Three walking-driven modes (steel catenary riser (SCR) tension, downslope, and thermal transient) are considered, covering a wide range of influential parameters. The variation in walking rate with respect to the effect of increased soil friction is well reflected in the development of the effective axial force (EAF) profile. A method based on the previous analytical solution is proposed for predicting the accumulated walking rates throughout the entire service life, where the concept of equivalent soil friction is adopted.

Biogrouting of hydraulic fill fine sands for reclamation projects - Jijian Lian; Hongyin Xu; Xiaoqing He; Yue Yan; Dengfeng Fu; Shuwang Yan; Hao Qi (Marine Georesources & Geotechnology, 2019)

Isolation and characterization of an antimicrobial peptide from bovine hemoglobin α-subunit - Jianhe Hu; Minglu Xu; Bolin Hang; Lan Wang; Qing Wang; Junjie Chen; Tao Song; Dengfeng Fu; Ziliang Wang; Sanhu Wang; Xingyou Liu (World Journal of Microbiology and Biotechnology, 2011)